Neoadjuvant Treatment in Patients With Resectable and Borderline Resectable Pancreatic Cancer - Janssen, Quisette P.; O'Reilly, Eileen M.; van Eijck, Casper H. J.; Groot Koerkamp, Bas (Frontiers in Oncology, 2020)
Approximately 20% of pancreatic ductal adenocarcinoma (PDAC) patients have (borderline) resectable pancreatic cancer ((B)RPC) at diagnosis. Upfront resection with adjuvant chemotherapy has long been the standard of care for these patients. However, although surgical quality has improved, still about 50% of patients never receive adjuvant treatment. Therefore, recent developments have focused on a neoadjuvant approach. Directly comparing results from neoadjuvant and adjuvant regimens is challenging due to differences in patient populations that influence outcomes. Neoadjuvant trials include all patients who have (B)RPC on imaging, while adjuvant-only trials include patients who underwent a complete resection and recovered to a good performance status without any evidence of residual disease. Guidelines recommend neoadjuvant treatment for BRPC patients mainly to improve negative resection margin (R0) rates. For resectable PDAC, upfront treatresection is still considered the standard of care. However, theoretical advantages of neoadjuvant treatment, including the increased R0 resection rate, early delivery of systemic therapy to all patients, directly addressing occult metastatic disease, and improved patient selection for resection, may also apply to these patients. A systematic review by intention-to-treat showed a superior median overall survival (OS) for any neoadjuvant approach (19 months) compared to upfront surgery (15 months) in (B)RPC patients. A neoadjuvant approach was recently supported by three randomized controlled trials (RCTs). For resectable PDAC, neoadjuvant treatment was superior in a Japanese RCT of neoadjuvant gemcitabine with S-1 versus upfront surgery, with adjuvant S-1 in both arms (median OS: 37 vs. 27 months, p = 0.015). A Korean trial of neoadjuvant gemcitabine-based chemoradiotherapy versus upfront resection in BRPC patients was terminated early due to superiority of the neoadjuvant group (median OS: 21 vs. 12 months, p = 0.028; R0 resection: 52 vs. 26%, p = 0.004). The PREOPANC-1 trial for (B)RPC patients also showed favorable outcome for neoadjuvant gemcitabine-based chemoradiotherapy versus upfront surgery (median OS: 17 vs. 14 months, p = 0.07; R0 resection: 63 vs. 31%, p < 0.001). FOLFIRINOX is likely a better neoadjuvant regimen, because of superiority compared to gemcitabine in both the metastatic and adjuvant setting. Currently, five RCTs evaluating neoadjuvant modified or fulldose FOLFIRINOX are accruing patients.